Dampak Kontrol Fokus, Keberanian, Keterbukaan terhadap Kinerja Akademik Siswa Implikasi bagi Dunia Pendidikan Teknik - Sisrayanti; Ambiyar; Lapisa, Remon; Sabrina, Elsa (The Indonesian Journal of Computer Science, 2024)
Education is a crucial pillar in shaping individuals and organizational success. The interconnectedness between them is a primary focus in enhancing the quality of education and human resource development. This research examines the relationship between psychological factors such as Kontrol Fokus, Keberanian, and openness with Kinerja Akademik Siswa. In an ever-evolving era, a deeper understanding of these psychological factors is essential. It is hoped that this study provides insight into how Kontrol Fokus aids in task management, the role of Keberanian in facing challenges, and how openness stimulates innovative thinking and adaptation, thereby facilitating shared goals. The research's conclusion emphasizes the importance of close collaboration in education to tackle complex challenges and achieve future success. Understanding individual psychology is also key to optimizing human potential and organizational goals attainment.